The effects of IPPB on ventilation distribution in high risk adults following open upper abdominal surgery using electrical impedance tomography - Ross, Nicolette Hayley (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScPhysio)--Stellenbosch University, 2015.